The impact of Trade Liberalisation on Formal Sector Employment in Ghana - Hormeku-Adjei, Reindorf Kwesi (2011)
A thesis submitted to the Department of Economics, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the award of Master of Arts (Economics) degree.